Comparative analysis of the Leibniz’s and Wolff’s concepts of system - Secundant, Sergii (Sententiae, 2020)
If Wolff from the very beginning was strongly influenced by Cartesianism, and his concept of system was guided by the geometric model of scientific method, Leibniz relies on the German tradition of “methodological thinking”, originated by Joachim Jung. Leibniz’s conception of system focuses mainly on algebraic analysis. The application of the term “system” mainly to metaphysics can be explained by the fact that it is this science that deals with synthetic principles and is designed to develop a rational view of the world. Based on the idea of “real metaphysics”, Leibniz justifies these principles as such that make possible the laws of physics and rational discourse in general. Leibniz does not provide a system of philosophy in the sense of traditional school philosophy. He considers metaphysics as the most consistent expression of a systematic mind and indicates heuristic principles for the construction and improvement of reasonable hypotheses.